Filarial Pleural Effusion with Lymphoma: A Rare Association - Kiran Agarwal; Aruna Chhikara (Journal of Clinical and Diagnostic Research, 2019)
Filariasis is endemic in developing countries with highest prevalence in India. Microfilarias are infrequently reported during cytological examination of body cavity fluids. Its association with neoplasm is still rare, with only a few reported cases of co-existent microfilaria with neoplasm. The malignancies reported in association with malignant pleural effusions are mostly carcinomas. Finding microfilaria in a pleural effusion is a very rare event even in the regions endemic for this organism. Its association with a lymphoma is even rarer. On extensive search of literature we could not find any case report of filarial pleural effusion associated with lymphoma. We here report a case of microfilaria in malignant pleural effusion secondary to lymphoma.